Preliminary Physicochemical screening of bioactive based nanocarrier system - Srivastava, Rajnish; Choudhury, Pratim Kumar; Dev, Suresh Kumar; Rathore, Vaibhav (Journal of Drug Delivery and Therapeutics, 2020)
The roles of oxidative stress (OS) in neurodegenerative diseases, the manipulation of ROS levels may represent a treatment option to slow down neurodegeneration and alleviate associated symptoms. Many compounds with antioxidant properties have been examined for their potential to attenuate neurodegenerative symptoms. The drawbacks of oral administration of antioxidants are limited entry across the blood–brain barrier. Most molecules suffer from problems of solubility, bioavailability or the ability to cross the blood brain barrier and hence nanomedicine needs to be explored. The excipient components (Carrier oil, surfactant and co-surfactant) were selected on the basis of their miscibility in alpha-pinene. The miscibility of the drug was assessed in 25 carrier oil, 5 surfactant and 6 Co-surfactant. Total 250 self-nanoemulsifying nanoformulations (SENF) compositions were prepared from the selected excipients and were preliminary screened on the basis of the number of flask inversion, emulsification time and stability up to 72 hours. Three SNEDDS formulation compositions finally selected for the development and optimization for excipient concentration as these combinations was found to possessed no. of flask inversion and emulsification time. Keywords: Self-nanoemulsifying nanoformulations, Bioavailability, Alpha-pinene, oxidative stress, blood–brain barrier